Cancer‐like metabolism of the mammalian retina. (7th November 2014) - Ng, Soo Khai; Wood, John PM; Chidlow, Glyn; Han, Guoge; Kittipassorn, Thaksaon; Peet, Daniel J; Casson, Robert J
Abstract The retina, like many cancers, produces energy from glycolysis even in the presence of oxygen. This phenomenon is known as aerobic glycolysis and eponymously as the Warburg effect. In recent years, the Warburg effect has become an explosive area of study within the cancer research community. The expanding knowledge about the molecular mechanisms underpinning the Warburg effect in cancer promises to provide a greater understanding of mammalian retinal metabolism and has motivated cancer researchers to target the Warburg effect as a novel treatment strategy for cancer. However, if the molecular mechanisms underlying the Warburg effect are shared by the retina and cancer, treatments targeting the Warburg effect may have serious adverse effects on retinal metabolism. Herein, we provide an updated understanding of the Warburg effect in mammalian retina.